2017
DOI: 10.1002/adhm.201700165
|View full text |Cite
|
Sign up to set email alerts
|

Cotransporting Ion is a Trigger for Cellular Endocytosis of Transporter‐Targeting Nanoparticles: A Case Study of High‐Efficiency SLC22A5 (OCTN2)‐Mediated Carnitine‐Conjugated Nanoparticles for Oral Delivery of Therapeutic Drugs

Abstract: OCTN2 (SLC22A5) is a Na -coupled absorption transporter for l-carnitine in small intestine. This study tests the potential of this transporter for oral delivery of therapeutic drugs encapsulated in l-carnitine-conjugated poly(lactic-co-glycolic acid) (PLGA) nanoparticles (LC-PLGA NPs) and discloses the molecular mechanism for cellular endocytosis of transporter-targeting nanoparticles. Conjugation of l-carnitine to a surface of PLGA-NPs enhances the cellular uptake and intestinal absorption of encapsulated dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 29 publications
5
62
0
Order By: Relevance
“…Of them, caveolin-dependent endocytosis was preferred by LC-PLGA NPs. The difference of endocytosis mechanism between PLGA NPs and LC-PLGA NPs might be due to the conjugation of L-carnitine [30,37]. These data strongly implicate that OCTN2-mediated endocytosis are involved in the cellular uptake of LC-PLGA NPs.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Of them, caveolin-dependent endocytosis was preferred by LC-PLGA NPs. The difference of endocytosis mechanism between PLGA NPs and LC-PLGA NPs might be due to the conjugation of L-carnitine [30,37]. These data strongly implicate that OCTN2-mediated endocytosis are involved in the cellular uptake of LC-PLGA NPs.…”
Section: Discussionmentioning
confidence: 72%
“…It has been suggested that the interaction of ligands with targets on cell surface mostly occurs through multivalent binding [26,30,38,39]. Therefore, it is reasonable that the PEG spacer length of ligand attached to nanoparticle surface would affect the binding of ligand to the target, and thus influence the target efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy involves facilitative glucose transporter 1 (GLUT1and SLC2A1), Na þ /Cl À -coupled amino acid transporter (ATB 0,þ and SLC6A14), facilitative amino acid exchanger large neutral amino acid transporter (LAT1 and SLC7A5) and so on [14][15][16][17][18][19]. What's more, in the latest progress of our research, we found that L-carnitine-conjugated nanoparticles (LC-PLGA NPs) selectively targeted to organic cation transporter 2 (OCTN2 and SLC22A5) on the enterocytes for enhancing oral delivery of drugs [20][21][22]. The results greatly encouraged us that transporter-mediated NPs with specific ligands as a formulation hold potential for the application of orally administrated therapeutics.…”
Section: Introductionmentioning
confidence: 79%
“…These findings suggest that the transporter protein is not recycled following endocytosis, but instead gets degraded. The endocytic mechanisms of LC-PLGA NPs have been investigated in our previous study (Kou et al, 2017), suggesting that clathrin-mediated, caveolin-mediated endocytosis, and macropinocytosis were involved in the endocytic process. Except for caveolin-mediated endocytosis, the endosomes containing nanoparticles and transporters would get fused with lysosomes for clathrin-mediated endocytosis and macropinocytosis, resulting in drug release and transporter degradation (Kou et al, 2013).…”
Section: Discussionmentioning
confidence: 94%